2007
DOI: 10.1111/j.1751-0813.2007.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of canine parvovirus from dogs in Australia

Abstract: CPV-2a remains the predominant genetic variant of CPV in dogs in Australia and has not been replaced by CPV-2b or CPV-2c as in many other countries. The vaccine failures investigated in the study were likely caused not by genetic variation of field viruses but by maternal antibody interference in the response of pups to vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 24 publications
7
58
0
Order By: Relevance
“…There are some reports suggesting that CPV-2b may cause a milder disease than CPV-2a viruses (17,18); however, both CPV-2a and 2b have been detected in animals with severe diarrhea (14). Although the main purpose of this study was the genomic typing of CPV strains circulating in Rio de Janeiro, it should be noted that most of the "new CPV-2a" samples (16/19) were collected from puppies with a more severe enteric disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some reports suggesting that CPV-2b may cause a milder disease than CPV-2a viruses (17,18); however, both CPV-2a and 2b have been detected in animals with severe diarrhea (14). Although the main purpose of this study was the genomic typing of CPV strains circulating in Rio de Janeiro, it should be noted that most of the "new CPV-2a" samples (16/19) were collected from puppies with a more severe enteric disease.…”
Section: Resultsmentioning
confidence: 99%
“…(2). At present, CPV-2c is broadly distributed in Italy (16), and has also been found in Spain (8), Germany, the United Kingdom (9), the United States (13), Australia (17), and Portugal (27). Although the first reports seemed to show a low pathogenicity for CPV-2c, experimental data and field observations now indicate that a more severe clinical course with higher mortality rates is associated with CPV-2c infection (10).…”
Section: Introductionmentioning
confidence: 97%
“…The same variant was later detected in other European countries ), Asia (Nakamura et al 2004), Australia (Meers et al 2007), North and South America countries including Brazil (Hong et al 2007, Pérez et al 2007, Streck et al 2009). …”
Section: Introductionmentioning
confidence: 94%
“…CPV infection has been reported from Africa, Asia, Australia, the Americas and Europe (Steinel et al, 1998;Decaro et al, 2007;Meers et al, 2007;Kumar & Nandi, 2010;Markovich et al, 2012;P erez et al, 2012;Castanheira et al, 2014), and there are large numbers of publications which have reported the frequencies of different CPV variants in various countries and regions. Table 1 summarizes the presence of the CPV variants around the world in the domestic dog population, based on the analysed references.…”
Section: The Worldwide Distribution Of Antigenic Cpv-2 Variants Spreamentioning
confidence: 99%
“…Recent epidemiological reports indicate that CPV-2a with VP2 426Asn is the predominant variant in Australia (Meers et al, 2007), most of Asian (Yoon et al, 2009, Phromnoi et al, 2010Chou et al, 2013;Yi et al, 2014;Timurkan et al, 2015) and European countries (Ntafis et al, 2010;Decaro et al, 2011Decaro et al, , 2013Cavalli et al, 2014;Filipov et al, 2014), and this is the only variant reported in New Zealand (Ohneiser et al, 2015), Nigeria (Dogonyaro et al, 2013), Hungary (Demeter et al, 2010), Czech Republic , Slovenia and Romania (Decaro et al, 2012), while it was not detected in Vietnam and Mexico, as well as, from an outbreak in a litter in Sweden (Table 1, Fig. 4).…”
Section: The Worldwide Distribution Of Antigenic Cpv-2 Variants Spreamentioning
confidence: 99%